Leiomyoma of the vulva; a rare occurrence - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Leiomyoma are known to occur in the uterus. It is unusual to find these benign smooth muscle tumours anywhere else. We report the occurrence of a swelling that appeared like a huge Bartholin’s cyst in the vulva of a 30 year old married nulliparous woman. She had successful excision and histology confirmed it to be a leiomyoma.